2017
DOI: 10.1097/brs.0000000000002121
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Financial Relationships Between Spine Surgeons and Industry

Abstract: 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 32 publications
0
23
1
Order By: Relevance
“…Considering that orthopedic surgeons receive the greatest total value of industry support and neurosurgeons represent the highest proportion of industry relationships, it is important for us to analyze the implications of industry support on the field and cost of spinal surgery. 1,2 Our current study revealed no association between industry payments received by spine surgeons and the total hospital cost, or operating room cost, of an ACDF operation in Medicare patients. When stratified by quartile of industry payment received, there were no significant differences in either the mean or median total cost, or operating room cost, for an ACDF.…”
Section: J O U R N a L P R E -P R O O Fcontrasting
confidence: 46%
See 2 more Smart Citations
“…Considering that orthopedic surgeons receive the greatest total value of industry support and neurosurgeons represent the highest proportion of industry relationships, it is important for us to analyze the implications of industry support on the field and cost of spinal surgery. 1,2 Our current study revealed no association between industry payments received by spine surgeons and the total hospital cost, or operating room cost, of an ACDF operation in Medicare patients. When stratified by quartile of industry payment received, there were no significant differences in either the mean or median total cost, or operating room cost, for an ACDF.…”
Section: J O U R N a L P R E -P R O O Fcontrasting
confidence: 46%
“…A recent study of 5,898 spine surgeons in the Open Payments database found that orthopedic (versus neurosurgery) training, academic practice setting, male gender, practice in the Western or Southern U.S., and younger age were strongly associated with industry relationships. 1 Another recent study found that most surgeons were not aware of operative costs and that, when implemented, cost feedback was significantly associated with a reduction in the cost J o u r n a l P r e -p r o o f of surgical supplies. 16 As such, cost feedback may be an integral step towards curbing the cost of expensive surgical procedures like spinal fusions.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
See 1 more Smart Citation
“…15,19 The disproportionate amount of payments to orthopaedic surgeons is potentially explained by the devicedriven nature of the field. Other studies of payments to orthopaedic surgeons from industry sources based on the OPD were somewhat limited in that they described only the data set, 11,23,27 did not assess accuracy of self-disclosures, 11,21 or assessed the accuracy of nonpublication self-disclosures (eg, disclosures from orthopaedic conferences). 14 Relatively little is known about the accuracy of conflict of interest disclosures among high-impact factor orthopaedic journals.…”
mentioning
confidence: 99%
“…Because the OPD does not contain information about the gender of doctors, authors of articles used one or more different methods to obtain this information. These were methods such as: looking at the National Provider Index data set (Weiss et al , 2018; Qian et al , 2017; Marshall et al , 2016; Muffly et al , 2018; Perlis and Perlis, 2016; Tringale et al , 2017); viewing a physician’s practice or academic profile (Boddapati et al , 2018); conducting internet searches for doctors’ profiles, pictures, hospitals and departmental websites (Weiss et al , 2018; Weiner et al , 2017; Eloy et al , 2017a; Eloy et al , 2017b; Weng et al , 2019; Feng et al , 2016; Hopkins et al , 2019); and cross-referencing different public or third-party data sources (e.g. the American Academy of Ophthalmology, and state licensure systems) with the OPD database (Qian et al , 2017; Brunt, 2019; Weng et al , 2019; Weiss et al , 2018; Muffly et al , 2018; Reddy et al , 2016).…”
Section: Resultsmentioning
confidence: 99%